P-66 Hospices in harmony: the community choir phenomenon. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Simpson, Fraser; Ambrose, Ana
Abstract : Background: The benefits of singing have been well documented in recent years and include physical, psychological, cognitive and social benefits (Clift et al., 2008). Many hospices today offer singing activities of various kinds and this has become something of a phenomenon in contemporary hospice services. However, there is little or no research to date about why hospice singing has taken off around the country with such resounding success. The Earl Mountbatten Hospice (EMH) Community Choir (Isle of Wight) launched in January 2017, directed by the hospice's music therapist. Meeting weekly on a weekday evening, it had immediate impact, drawing in patients, relatives, staff and volunteers from the hospice community in large numbers. Aims: A qualitative research project is currently underway which aims to explore the subjective experiences of choir participants in order to understand better the hospice choir phenomenon. Methods: The project comprises a series of focus groups that are being recorded, transcribed and analysed in an effort to find out: What are the specific benefits for members of the hospice community of singing in the choir? What is the particular experience for choir members of being part of a mixed choir representing different 'groups' from the hospice community (patients, staff etc)? Results: The project aims to highlight the social and relational factors that improve participants' perceptions of the hospice environment and increase a sense of community. Conclusion: This illustrated presentation will profile the EMH Community Choir, and will outline the completed research conclusions. The implications for hospices which run (or are considering running) choirs will be explored; this will also include reflections on how the choir has impacted on the life of the organisation, and an examination of the skills needed to run a successful hospice choir.